2022
DOI: 10.1155/2022/7445042
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Exploration of the Effects of TGF‐β Pathway‐Based Pituitary Tumor of Rats on GH3 Cell Line after Intervention with Different Concentrations of TGZ

Abstract: The effect of the TGF-β pathway-based pituitary tumor of rats on the GH3 cell line after intervention with different concentrations of troglitazone (TGZ) is explored. The CH3 cell line of 24 clean male SD rats with pituitary adenoma is selected. The cells are divided into a blank contrast set and an experimental set. The experimental set is divided into different TGZ concentration sets, including 1 × 10−3 TGZ set, 1 × 10−4 TGZ set, and 1 × 10−5 TGZ set. The cell proliferation is detected by the CCK-8 method, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Moreover, Duan et al tested Tioglitazione ("TGZ", an agonist of PPAR-c) as a potential therapeutic agent. They demonstrated that somatotroph cellular lines exposed to increasing concentrations of TGZ reduced the expression of TGF-β [132].…”
Section: Transforming Growth Factor Receptormentioning
confidence: 99%
“…Moreover, Duan et al tested Tioglitazione ("TGZ", an agonist of PPAR-c) as a potential therapeutic agent. They demonstrated that somatotroph cellular lines exposed to increasing concentrations of TGZ reduced the expression of TGF-β [132].…”
Section: Transforming Growth Factor Receptormentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%